Salad Days: Urban Food Futures. (1st September 2021) - Lloyd, Scott; Kalagas, Alexis
Abstract: Food production has never been entirely absent from our cities. While the coronavirus pandemic has imposed and inspired new forms of localism in urban environments, a confluence of technological, societal and ecological forces was already driving a shift towards more distributed and circular food systems. Scott Lloyd, architect and director of the design research group TEN, and Alexis Kalagas, strategic designer and leader of an advanced architecture research unit at Monash University in Melbourne, navigate and speculate on these intersecting dynamics in relation to nascent models of urban food production.